PERLINDUNGAN TERHADAP HAK-HAK NORMATIF KARYAWAN AKIBAT PEMUTUSAN HUBUNGAN KERJA PADA PERUSAHAAN PT. FEDERAL INTERNATIONAL FINANCE DENPASAR - Alit Jaya Praditha, I Gusti Ngurah; Mudana, I Nyoman; Darmada, I Nyoman (Kertha Desa, 2013)
Termination is one thing that marks the end of the employment relationshipbetween employers. The problem that arises is about the rights of labor or employeewill be accepted, can be obtained or not by the individual as a result of thetermination. The basic rights that should be accepted as a result of termination isseverance pay, gratuity and compensation.
Keywords: Termination of employment, workers' basic rights.